Relación entre las funciones ejecutivas y el bullying en niños y adolescentes escolarizados: revisión aplicada - Echeandia Vargas, Andrea (2023)
Bullying interferes with the physical, cognitive and social development of children and adolescents in the school context. Executive functions (EF) are essential so that individuals can develop adaptive responses to the demands of the environment. When they do not achieve this, the probability of them becoming involved in this problem increases. The objective of the present systematic review was to identify the relationship between EF and bullying in school-going children and adolescents. Two databases were used, inclusion and exclusion criteria were identified, from which 10 articles were selected. The results reveal significant bivariate correlations between EF difficulties and bullying, as well as predictive associations. The discussion is carried out based on the main and secondary findings, where, through multivariate analysis, a relationship was found with school resources and psychological disturbance. Relevant interventions in the field of psychology are shared. It is concluded that there is a bivariate and negative correlation, as well as predictive associations, between EF difficulties and bullying. These difficulties have a moderating role on victimization and perpetration, and a mediating role between the effect of school resources on bullying.